1986
DOI: 10.1139/z86-399
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial DNA restriction site variation in the Townsend's vole, Microtus townsendii

Abstract: The mitochondrial DNA (mtDNA) from the Townsend's vole, Microtus townsendii, was compared with mouse mtDNA by positioning vole restriction enzyme fragments on the known laboratory mouse mtDNA molecule by homology hybridization. The vole mitochondrial genome is conserved in general sequence organization and size but does contain a nonhomologous region of more than 600 base pairs not found in the mouse sequence. Thirty-five voles were collected from seven different localities throughout the range of the species,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

1989
1989
2001
2001

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 9 publications
1
4
0
Order By: Relevance
“…The levels of intraspecific nucleotide divergence displayed between rainbow trout and steelhead populations as measured by this technique are very similar to mtDNA sequence divergence determined for populations of Microtus townsendii (vole) collected from a comparable, although smaller geographic area of the Pacific northwest (Thomas 1984). These populations also showed divergence of less than 1%.…”
Section: Discussionsupporting
confidence: 68%
“…The levels of intraspecific nucleotide divergence displayed between rainbow trout and steelhead populations as measured by this technique are very similar to mtDNA sequence divergence determined for populations of Microtus townsendii (vole) collected from a comparable, although smaller geographic area of the Pacific northwest (Thomas 1984). These populations also showed divergence of less than 1%.…”
Section: Discussionsupporting
confidence: 68%
“…Our analysis reveals that M. pennsylvanicus and M. townsendii are well separated and that the meadow vole samples could be clustered into two major groups, the central and the eastern Canadian populations, with no apparent geographical ordering within the eastern group. The lack of concordance between phylogeny and local geography has been rarely observed in small mammals (but see Thomas and Beckenbach 1986), although it seems to be typical of the American eel (Anguilla rostrata) For personal use only. and humans (Brown 1980;Cann et al 1987).…”
Section: Mtdna Variability Between Populationsmentioning
confidence: 99%
“…It is noteworthy that Thomas and Beckenbach (1986) had a similar experience to ours when they used DNA hybridization to map mtDNA restriction fragments from another microtine, Microtus townsendii. In their investigation, a 700-bp Hind III fragment that mapped to the region of the ND5-ND6 genes failed to hybridize to any portion of the mouse mtDNA genome, and it was suggested that the 700-bp fragment might be nonhomologous to mouse mtDNA (Thomas and Beckenbach 1986).…”
Section: Introductionmentioning
confidence: 65%
“…In their investigation, a 700-bp Hind III fragment that mapped to the region of the ND5-ND6 genes failed to hybridize to any portion of the mouse mtDNA genome, and it was suggested that the 700-bp fragment might be nonhomologous to mouse mtDNA (Thomas and Beckenbach 1986). These observations seem to suggest that some regions of the microtine genome might be unusually divergent from that of mice.…”
Section: Introductionmentioning
confidence: 99%